Instalasi dan Sosialisasi Teknologi Solar Panel System Untuk Penerangan Pura di Banjar Jematang Denpasar Barat - Made Dika Nugraha; Kadek Agus Mahabojana Dwi Prayoga; Kadek Diviariesty (Postgraduated Community Service Journal, 2024)
Community service in Banjar Jematang Denpasar is a form of campus concern for its environment, both the general public, government and village officials covering the Denpasar city area, especially West Denpasar sub-district, giving complaints because the road to the temple is dark at night and the community's desire to reduce bills PLN electricity, especially for temples which still rely on cash from the Hindu temple community for operational costs. Considering that currently the need for lighting is high for Hindus when praying at night, temple street lighting has electricity source technology such as a solar panel system that is capable of running without being connected to paid PLN electricity. This service will involve traditional services, service services and 4 visitors, respectively, Puseh temple, Mojopahit temple and Maospait temple. It is hoped that the results of the service will help partners and be able to understand and continue the application of the tool and in the future the system can be developed to advance technology in the Denpasar city area.